2002
DOI: 10.1128/jcm.40.8.2849-2853.2002
|View full text |Cite
|
Sign up to set email alerts
|

Role of Corpus Gastritis and cagA -Positive Helicobacter pylori Infection in Reflux Esophagitis

Abstract: Considering that the role of Helicobacter pylori infection in gastroesophageal reflux and reflux esophagitis (GERD) is still controversial and that the role of virulence markers of the bacterium has not been evaluated in most studies of GERD, we investigated the association among H. pylori infection with cagA-positive and -negative strains, corpus gastritis, and GERD in a large group of patients by controlling for confounding factors. We studied prospectively 281 consecutive adult patients: 93 with GERD and 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 32 publications
1
17
0
5
Order By: Relevance
“…Several studies have provided evidence supporting the protecting role of cagA-positive H. pylori strains against GERD [59, [60], [61], [62]and [63], but these results were not confirmed by others [64], [65]. On the contrary,there was a significant increase in cagA-positive H. pylori strains in GERD (70%) [66].…”
Section: )[32]mentioning
confidence: 91%
“…Several studies have provided evidence supporting the protecting role of cagA-positive H. pylori strains against GERD [59, [60], [61], [62]and [63], but these results were not confirmed by others [64], [65]. On the contrary,there was a significant increase in cagA-positive H. pylori strains in GERD (70%) [66].…”
Section: )[32]mentioning
confidence: 91%
“…In Brazil, PEREIRA-LIMA et al (31) concluded that H. pylori gastric infection and especially H. pylori CagA-positive may play a protective role against the development of the most severe forms of GERD. On the other hand in this study, the patients had dyspepsia, peptic ulcer and erosive gastritis, differently that our study, in which all patients homogeneously had peptic ulcer disease.…”
Section: Discussionmentioning
confidence: 99%
“…Recentemente, alguns trabalhos mostram que a infecção pelo H. pylori poderia ter um efeito protetor contra a doença (17,18,33,45,57) . De modo complementar, mostrou-se que pacientes infectados por linhagens mais virulentas (cagA+, vacAs1) estariam inversamente associados com o desenvolvimento da doença.…”
Section: Resultsunclassified
“…De modo complementar, mostrou-se que pacientes infectados por linhagens mais virulentas (cagA+, vacAs1) estariam inversamente associados com o desenvolvimento da doença. Deste modo, pacientes infectado por tais linhagens seriam protegidos contra complicações decorrentes do refluxo ácido (17,33,45,57) . Algumas hipóteses têm sido propostas para explicar tal fenômeno.…”
Section: Resultsunclassified
See 1 more Smart Citation